Ichimoku Kinko Hyo: Keunikan dan Penerapannya dalam Strategi Perdagangan Valuta Asing (Studi Kasus pada Pergerakan USD/JPY dan EUR/USD) - Cahyadi, Yoyo (Bina Nusantara University, 2012)
Ichimoku Kinko Hyo is a technical analysis tool that can be used to predict the movement of a currency. Ichimoku Kinko Hyo has five components or indicators, they are Tenkan Sen (or Conversion Line), Kijun Sen (or Base Line), Chikou Span (or Lagging Span), Senkou Span A and Senkou Span B. This paper discusses the application of Ichimoku Kinko Hyo in predicting the movement of USD/JPY and EUR/USD. Daily and hourly chart have been used to conduct the analysis. The observation shows that Ichimoku Kinko Hyo relatively easier to be applied in daily chart. Ichimoku Kinko Hyo can give a prediction whether a currency pair will move in a trend or consolidation.